2018
DOI: 10.1186/s12879-018-2988-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B/C in the countries of the EU/EEA: a systematic review of the prevalence among at-risk groups

Abstract: BackgroundIn 2016, the World Health Organisation set a goal to eliminate viral hepatitis by 2030. Robust epidemiological information underpins all efforts to achieve elimination and this systematic review provides estimates of HBsAg and anti-HCV prevalence in the European Union/European Economic Area (EU/EEA) among three at-risk populations: people in prison, men who have sex with men (MSM), and people who inject drugs (PWID).MethodsEstimates of the prevalence among the three risk groups included in our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
104
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 57 publications
11
104
1
4
Order By: Relevance
“…These findings are similar to those reported by Adoga [19]. In the prison milieu, overcrowding and precarious conditions with increased promiscuity favours this practice which is well known as risk factor of HCV infection.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are similar to those reported by Adoga [19]. In the prison milieu, overcrowding and precarious conditions with increased promiscuity favours this practice which is well known as risk factor of HCV infection.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, prisoners are prone to hide their real injection status. However, the ndings of a study by Falla et al in Europe showed that the prevalence of HBV and HCV in prisoners is higher than that among injecting drug users (3). It highlights the fact that imprisonment results in the gathering of a large group of patients and provides a chance to implement health-related interventions, including diagnosis, treatment, and prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a large proportion of cases with HBV and HCV are exclusively observed in speci c groups such as prisoners and people who inject drugs (PWID) (3), that might be attributed to different reasons. First, a signi cant percentage of prisoners are incarcerated due to drug-related crimes (4), therefore, there is a high population of PWID in prisons.…”
Section: Introductionmentioning
confidence: 99%
“…Global HCV seroprevalence among MSM living with HIV was estimated at 6.4% from 2002-2015 [11]. Comparatively, the burden of HCV has remained stable among HIV-negative MSM, with estimates of HCV seroprevalence ranging from 0.0-3.4% [12][13][14][15][16], and a global incidence of 0.4/1,000 person-years [17]. Nevertheless, recent cases of acute HCV infection have been reported among HIV-negative MSM without a history of injection drug use (IDU) in Europe [18], the United States [19], and Vancouver, British Columbia (Canada) [20].…”
Section: Introductionmentioning
confidence: 99%